2017
DOI: 10.1108/ijmhsc-10-2015-0036
|View full text |Cite
|
Sign up to set email alerts
|

Are visible minorities “invisible” in Canadian health data and research? A scoping review

Abstract: Purpose Canada’s visible minority population is increasing rapidly, yet despite the demographic significance of this population, there is a surprising dearth of nationally representative health data on visible minorities. This is a major challenge to undertaking research on the health of this group, particularly in the context of investigating racial/ethnic disparities and health disadvantages that are rooted in racialization. The purpose of this paper is to summarize: mortality and morbidity patterns for visi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 51 publications
1
41
0
2
Order By: Relevance
“… 26 27 However, South Asians are under-represented in research, resulting in healthcare practice based on research with limited external validity for the South Asian context. 28 29 In general, there is a lack of representative population health research comparing minority groups in Canada with European counterparts. 28 This under-representation also occurs elsewhere; a UK-based analysis reported that while South Asians make up 4.5% of the total population, they represented on average only 0.6% of participants in six multicentre randomised controlled trials.…”
Section: Introductionmentioning
confidence: 99%
“… 26 27 However, South Asians are under-represented in research, resulting in healthcare practice based on research with limited external validity for the South Asian context. 28 29 In general, there is a lack of representative population health research comparing minority groups in Canada with European counterparts. 28 This under-representation also occurs elsewhere; a UK-based analysis reported that while South Asians make up 4.5% of the total population, they represented on average only 0.6% of participants in six multicentre randomised controlled trials.…”
Section: Introductionmentioning
confidence: 99%
“…Today, both language and culture are recognized as the determinants of health and access to health care. 13,14 Linguistic barriers are associated with increased risk of hospital admission, errors in prescribed medication, greater number of reported adverse drug reactions, and lower rates of pain medication. 15 Specifically, lack of comprehension poses a serious limitation on access to health care services, adherence to medication regimens, and consent to essential procedures in older Francophone adults living in a minority situation.…”
Section: Language Culture and Healthmentioning
confidence: 99%
“…Today, both language and culture are recognized as the determinants of health and access to health care . Linguistic barriers are associated with increased risk of hospital admission, errors in prescribed medication, greater number of reported adverse drug reactions, and lower rates of pain medication .…”
Section: Introductionmentioning
confidence: 99%
“…With regards to the Canadian context of this review, research on Indigenous Canadians, visible minorities, and immigrant populations would be salient as close to one-fifth of the Canadian population are members of a visible minority group (Khan, Kobayashi, Lee & Vang, 2015). Furthermore, although research about visible minorities and health is lacking, it is known that certain ethnic groups have a susceptibility to hypertension above others (Khan et al, 2015).…”
Section: Dose Dependent Effects Of MImentioning
confidence: 99%
“…Furthermore, although research about visible minorities and health is lacking, it is known that certain ethnic groups have a susceptibility to hypertension above others (Khan et al, 2015).…”
Section: Dose Dependent Effects Of MImentioning
confidence: 99%